Optimizing the Role of the Gorontalo High Prosecutor's Office in Realizing Restorative Justice - Nur, Rafika; Syamsidar; Djafar, Marwan (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Restorative justice is a legal approach aimed at repairing the effects of a criminal act by involving all parties in the conflict, including the perpetrator, the victim, and the community. The High Prosecutor's Office of Gorontalo plays a crucial role in realizing restorative justice in its region. This study aims to explore and optimize the role of the High Prosecutor's Office of Gorontalo in implementing restorative justice principles. This research aims to understand and optimize the role of the High Prosecutor's Office of Gorontalo in applying restorative justice principles. The method used is empirical research utilizing field data as the primary source, such as results from interviews and observations. The research findings indicate that optimizing the role of the High Prosecutor's Office of Gorontalo in realizing restorative justice in the Gorontalo Province turns the institution into a dignified law enforcement agency that enjoys high public trust in the law enforcement process, especially in criminal matters. Nowadays, the performance of law enforcement officers often becomes the focus of public scrutiny and criticism from the community and justice seekers who have long opined that the law is sharp towards the lower class and dull towards the upper class. This research provides a significant contribution to understanding how restorative justice can be an effective tool in the criminal justice system in Indonesia. It is expected that the process of case resolution based on restorative justice in the future will importantly see the range of bureaucratic control in its resolution shortened at the regional level up to the echelon II (High Prosecutor's Office) to expedite and make the case resolution process more flexible, and to maintain the accountability of the resolution of restorative justice cases, the prosecutorial ranks should strengthen supervision functions, both functional and inherent.